Investigating the dynamics of water and sediment disruption due to impeller action in silt-rich reservoir zones of inland waterways in China - Wang, Hao; Wang, Yu; Liu, Kaiqing; Luo, Tianfeng; Li, Jinping; Zhang, Ying; Miao, Tian; Tian, Miao; Wang, Zhehui; Zhang, Xiaolong (Frontiers in Earth Science, 2024)
Introduction: This study investigates the characteristics of sediment disturbance caused by impeller rotation in reservoirs of inland rivers with high sediment content in China. A scaled experimental model, reflecting typical environmental conditions of inland water reservoirs in Northwest China, was established in Lanzhou, Gansu Province, following the principle of similarity. Methods: The study integrates numerical simulations using Ansys Fluent software and corroborates the findings through hydraulic experiments. Computational Fluid Dynamics (CFD) and the κ–ε Realizable model were employed to simulate the solid-liquid mixing process, which was verified against the experimental model. Results: The results indicate that increasing the impeller velocity from 2 rad/s to 8 rad/s, while submerged at a depth of 1000 mm in the flow field, enhances the rate of bottom sediment suspension. Furthermore, the rate of suspended sediment discharge from the model outlet increased with inflow velocity ranging from 0.1 m/s to 0.8 m/s. A decrease in the impeller’s submersion depth from 600 mm to 1200 mm was found to reduce the maximum disturbance radius affecting the bottom sediment. Discussion: The reliability of the simulation was confirmed by comparing the software results with experimental data. This study provides insights into the mechanisms of sediment-laden flow disturbance in the reservoir areas of inland rivers in China and lays the groundwork for more comprehensive investigations into sediment discharge in these environments.